HUBUNGAN KEPERCAYAAN DIRI DENGAN PENYESUAIAN SOSIAL PADA REMAJA DI KELAS II SMP MUHAMMADIYAH 1 MALANG - Fitriah, Aziza (Faculty of Ushuluddin and Humanities, 2013)
The purpose of this research was to know whether there was a relationship between these two variables, howeverthose two variables were independence variable as self confidence and dependence variable as social adaptations. The type of this research was quantitative research (non-experiment). The respondents were 60 students of second grade in SMP Muhammadiyah 1 Malang. The supporting data of this research was gotten by observing and interviewing. And the collecting data technique used linkert scale questionnaire, and data analysis used correlation product moment by Karl Pearson. According to hypothesis test result could be taken the data between self confidence and social adaptation there was a significance correlations. Other wise the higher of teenage self confidence would make the teenage easier to do social adaptations with their social society around them.